Effective exchange to a larger size catheter for a lung abscess with initial percutaneous drainage failure: a case report - Maki Oh; Shohei Mori; Yuki Noda; Daiki Kato; Takashi Ohtsuka (Surgical Case Reports, 2020)
Abstract Background Percutaneous catheter drainage is an effective therapy for antibiotic-refractory lung abscesses. Pulmonary resection is usually considered in cases of drainage failure, although it remains controversial. Case presentation A 42-year-old man with antibiotic-refractory lung abscess underwent percutaneous abscess drainage with a 10-Fr pigtail catheter. However, adequate evacuation of the abscess content was not achieved, and his respiratory condition worsened and he required a ventilator. To achieve and maintain effective drainage, insertion of a larger size 28-Fr catheter to replace the 10-Fr catheter was performed under general anesthesia and one-lung ventilation with a double-lumen tube to isolate the left lung. Exchange with a larger size catheter was effective and achieved adequate drainage. The procedure was performed safely by expanding the route of the old catheter as a guide for accessing the abscess cavity. His condition immediately improved and he was discharged on day 40 post-catheter exchange with no complications and cured with a small residual thin wall cavity. Conclusions Small size catheters are generally recommended for initial percutaneous drainage; however, we argue that exchange with larger size catheters should be primarily considered instead of pulmonary resection in cases of initial drainage failure. This may avoid the need for pulmonary resection.